Thermoelectric Properties of Porous SiC/SiO2/C Composite from Carbonized Cryptomeria japonica Wood - Joko Sulistyo; Hiroyuki Kitagawa; Sri Nugroho Marsoem (Masyarakat Peneliti Kayu Indonesia, 2021)
Electric power generation by thermoelectric material utilizing radiated heat of from roof’s house, engine and others is potential clean energy in tropical areas such as Indonesia. In this study, thermoelectric materials such as silicon carbide (SiC/SiO2/C) composites were developed from carbonized Cryptomeria japonica wood infiltrated ethyl silicate-40 by sintering at 1400, 1600 and 1800 ºC for 30 min under N2 atmosphere. This study aimed to examine the morphology, microstructure and thermoelectric properties of porous SiC/SiO2/C composites. SiC/SiO2/C composites sintered at 1600 ºC with low value of thermal conductivity was potential for the development of thermoelectric material. The oxidation of SiC/SiO2/C composite sintered at 1600 °C which removed parts of residual silica and carbon, transformed the composite exhibiting p-type semiconductor with low values of Seebeck coefficient of to that exhibiting n-type semiconductor with high values Seebeck coefficient. A maximum of figure of merit of 6.25 x 10–5 K-1 was obtained at 140 ºC in the oxidized SiC/SiO2/C composite sintered at 1600 °C. The comparatively high figure of merit indicates the potentiality the material for thermoelectric purpose.